Desain Aplikasi Pemasaran Menggunakan E-Commerce di UMKM Batu Bata Riana: Design of a Marketing Application Using E-Commerce for the Batu Bata Riana MSMEs - Yusnawati, Yusnawati; Adlie, Taufan Arif; Masthura, Lely; Nadya, Yusri; Dewiyana, Dewiyana; Andriani, Meri; Handayani, Nurlaila; Zeki, Muhammad; Nurmalawati, Nurmalawati; Fadilah, Nahdah; Amalia, Sastika; Khatami, Muhammad; Nugraha, Aidil Rizky (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The Batu Bata Riana MSMEs located in Padang Langgis Village, Seruway Subdistrict, Aceh Tamiang Regency, is a micro-enterprise engaged in the production of red bricks using conventional production methods. Up until now, product marketing has primarily been carried out manually through word of mouth, resulting in limited market reach and low sales volume. This study aims to design and implement an online e-commerce-based marketing application, thereby expanding market reach and enhancing marketing effectiveness. The methodology includes partner needs analysis, user interface design, web-based application development, functionality testing, and user satisfaction evaluation. The resulting application features a product catalog, online ordering form, direct contact integration with the business owner, and location information display. The application has been implemented and is accessible via both mobile devices and desktop computers. Evaluation results indicate increased interest from new customers and potential sales volume growth of up to 30% compared to conventional marketing methods. These findings demonstrate that the application of e-commerce technology in brick-producing MSMEs has a positive impact on market expansion, transaction process efficiency, and business competitiveness in the digital era.